Implementing Public Policies with User Fees that Align with Partisan Ideology: A Canadian Example - Hache, Connie (Revue Gouvernance / Governance Review, 2016)
The Canadian federal government not only provides public services such as infrastructure, healthcare and education that benefit all citizens, but government also provides services on an individual basis to citizens. Through a case study, this paper explores how government makes decisions that support its political party’s ideology in deciding whether or not to implement user fees for services that benefit individuals. Using public choice theory, we discuss three actors with each actor striving to maximize their utility: elected officials by obtaining enough votes to form government; citizen-voters by obtaining more benefits than what they finance through general taxation; and pressure groups by spending resources on political activities to secure the group members’ preferences. We then apply these three actors to a case study: the decision to increase user fees for criminal record suspensions. The case study brings forth an example of government not acquiescing to the majority of citizen-voters’ and pressure groups’ demands if these demands do not align with government’s self-interest such as furthering their ideological stance.